2016
DOI: 10.18632/oncotarget.12678
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to neoplastic transformation ofex-vivoexpanded human mesenchymal stromal cells after exposure to supramaximal physical and chemical stress

Abstract: The risk of malignant transformation of ex-vivo expanded human mesenchymal stromal cells (huMSCs) has been debated in the last years; however, the biosafety of these cells after exposure to supramaximal physical and chemical stress has never been systematically investigated.We established an experimental in vitro model to induce supramaximal physical (ionizing radiation, IR) and chemical (starvation) stress on ex-vivo expanded bone marrow (BM)-derived huMSCs and investigated their propensity to undergo maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
3
10
0
Order By: Relevance
“…Our results are in agreement with many previous reports demonstrating that human MSC and ASC do not cause malignant growth [21][22][23][24][25]32]. Therefore, in contrary to induced pluripotent stem cells (iPS) cells that are known to induce multiple teratoma growth [73,74], in case of human MSC, so far, there is not enough evidence to suggest that application of extensively expanded MSC populations which might be enriched in c-MYC-overexpressing cells should be hindered by increased tumorigenesis risk.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results are in agreement with many previous reports demonstrating that human MSC and ASC do not cause malignant growth [21][22][23][24][25]32]. Therefore, in contrary to induced pluripotent stem cells (iPS) cells that are known to induce multiple teratoma growth [73,74], in case of human MSC, so far, there is not enough evidence to suggest that application of extensively expanded MSC populations which might be enriched in c-MYC-overexpressing cells should be hindered by increased tumorigenesis risk.…”
Section: Discussionsupporting
confidence: 89%
“…Even though no apparent accumulation of chromosomal aberrations or genetic mutations have been reported for MSC that undergone senescence due to prolonged ex vivo passaging [3,18], epigenetic changes associated with senescence, differentiation and alteration of immune response of these cells have been described [19,20]. The question whether MSC could undergo malignant transformation themselves or induce tumor growth remains controversial, as there have been reports ruling out a possibility of malignant transformation of MSC [21][22][23][24][25], as well as studies demonstrating that these concerns cannot be dismissed [26]. In respect of tumor pathogenesis, MSC could either promote and assist cancer cell growth [27] or undergo neoplastic transformation themselves [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Although the presence of high basal pATM expression in starving and starved cells was shown compared with regularly fed cells, we also saw that exposure of the starved and regularly fed cells to UV treatment resulted in a similar response, confirming that it is not stably hyperactivated in response to the starvation period. These data together confirmed that hBM-MSC have high resistance to genetic damage as previously demonstrated [36,37]. Although it has been shown that MSC have high metabolic flexibility [4][5][6], when cultured in vitro they have a glycolytic phenotype being highly dependent on glycolysis and glucose metabolism for energy.…”
Section: Discussionsupporting
confidence: 88%
“…These results were supported by the absence of trisomies or monosomies and structural abnormalities after starvation, as well as by the fact that starved cells retained their anchorage-dependent growth on soft agar. pATM, a central regulatory protein of the Damage Response Pathways (DDR), has been reported to contribute to the prevention of oncogenic transformation in MSC undergoing supramaximal stress [36]. Although the presence of high basal pATM expression in starving and starved cells was shown compared with regularly fed cells, we also saw that exposure of the starved and regularly fed cells to UV treatment resulted in a similar response, confirming that it is not stably hyperactivated in response to the starvation period.…”
Section: Discussionsupporting
confidence: 56%
“…On the other hand, multiple factors can still hamper MSC regenerative functions such as temperature, media type (Kubrova et al, 2019), interference of plastic adherence with cellular function (Mabuchi et al, 2012), chromosomal abnormalities, transformation, and tumor growth especially in MSCs of murine sources. Having said that, isolation and culture protocols recently developed for human MSCs derived from healthy subjects appear as promising endeavors to overcome those hurdles (Bernardo et al, 2007;Law and Chaudhuri, 2013;Conforti et al, 2016). For example, transformation and persistence were addressed in a protocol that uses skin tissue of patients undergoing any relevant medical intervention.…”
Section: Regenerative Propertiesmentioning
confidence: 99%